2018
DOI: 10.5144/0256-4947.2018.214
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping among consultant physicians working in Saudi Arabia

Abstract: BACKGROUNDExposure to stressful working conditions without adequate stress-coping strategies may lead to stress and even psychiatric morbidity. There are a dearth of studies on stress-coping strategies among consultant physicians in the Arabian Gulf.OBJECTIVESDetermine stress-coping strategies among consultants in Saudi Arabia and the relationship of strategies to level of stress.DESIGNAnalytical cross-sectional study.SETTINGSConducted between November 2014 and March 2015 among physician consultants registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 40 publications
4
34
1
6
Order By: Relevance
“…Regarding adaptive coping, the mean score for religion was the highest, followed by acceptance, and positive reframing, whereas for maladaptive coping, self-distraction had the highest mean and substance use had the lowest. Previous studies’ results on physicians and nurses in Saudi Arabia are consistent with the most and least frequent coping used; however, adaptive coping means were higher in comparison to our results [ 27 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding adaptive coping, the mean score for religion was the highest, followed by acceptance, and positive reframing, whereas for maladaptive coping, self-distraction had the highest mean and substance use had the lowest. Previous studies’ results on physicians and nurses in Saudi Arabia are consistent with the most and least frequent coping used; however, adaptive coping means were higher in comparison to our results [ 27 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Both the adaptive and maladaptive coping means in this study were higher than previous studies [ 39 ]. Both adaptive and maladaptive coping had higher means among consultant physicians in Saudi Arabia during non-pandemic periods [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adopting avoidant coping strategies is common among medical students. Previous studies found that avoidant stress-coping strategies were associated with psychiatric illness, shorter sleep duration, anxiety and depression [27][28][29]. Moreover, chronic stress was found to be associated with chronic fatigue, substance abuse and suicidal ideations among physicians [30].…”
Section: Discussionmentioning
confidence: 87%
“…A cross-sectional study involving consultant physicians (n = 582) found that more frequent use of an adaptive coping style was associated with lower stress levels among female physicians. 55 It is important to note that our participants had been in the UAE for a long period of time (mean: 16 years), and it is possible that they became acculturated and immersed in the UAE culture and learned to identify and positively cope with sources of stress. Participants were also more likely to live with their own families, who could perhaps be a source of emotional support for them.…”
Section: Discussionmentioning
confidence: 99%